Prevalence of cardiovascular risk factors among municipality workers in Chitradurga, South India - T., Nalina; Phasha, Ghouse; G., Prashanth; K., Sree Devi B. (International Journal of Advances in Medicine, 2019)
Background: Cardiovascular disease (CVD) is the single largest cause for mortality and morbidity in the world. In India, non-communicable diseases (NCDs) were responsible for 53% of deaths and 44% of disability adjusted life years lost. Appropriate assessment and management of cardiovascular risk is vital to prevent fatal and non-fatal heart attacks and strokes and to improve health outcomes in individuals at high risk of cardiovascular events. Diabetes mellitus (DM) and HT are common diseases in adulthood, pre-disposing to many cardiovascular complications, posing a major public health challenge. This study aims to assess the prevalence of cardiovascular risk factors such as diabetes, HT, smoking, alcohol intake, dyslipidaemia and obesity among Municipality workers. Methods: A cross-sectional study was carried out between Jan 2019-June 2019 among 100 Municipality workers in Chitradurga, South India. Socio-demographic details and some of the risk factors such as alcohol intake and smoking history were obtained using a pre-tested, structured questionnaire. Blood pressure & waist circumference were measured by standard methods. Fasting blood sugar & lipid profile were measured. Results: Mean age of study participants was 38.03 years (SD ± 10.9). Out of the study subjects, 21% were known diabetic and 22% were known hypertensive. 34% of the participants had cholesterol level higher than the desirable level of 200 mg/dL. Around 72% had a history of alcohol consumption and 13% had a history of tobacco smoking during the last 1 month. The prevalence of overweight based on BMI (BMI >23) is higher among Municipality workers (56%) compared to the general population (35.4%). Conclusions: Burden of cardiovascular risk factors such as diabetes and HT were high among Municipality Workers of Chitradurga.